2014
DOI: 10.1364/josab.31.001078
|View full text |Cite
|
Sign up to set email alerts
|

Artificial magnetism at terahertz frequencies from three-dimensional lattices of TiO_2 microspheres accounting for spatial dispersion and magnetoelectric coupling

Abstract: We employ the generalized Lorentz-Lorenz method to investigate how both magnetoelectric coupling and spatial dispersion influence the artificial magnetic capabilities at terahertz frequencies of the representative case of a metamaterial consisting of a three-dimensional (3D) lattice of TiO 2 microspheres. The complex wavenumber dispersion relations pertaining to modes supported by the array, traveling along one of the principal axes of the array with electric or magnetic field polarized transversely and longit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…In the following, we report on the mode coupling effect which plays a dominant role in the electromagnetic properties of metamaterials [33][34][35][36], notably, in the achievement of negative effective index. Magnetic and electric mode coupling effects in ADMs have been separately studied from each other in the microwave by Zhang et al [34].…”
Section: Introductionmentioning
confidence: 99%
“…In the following, we report on the mode coupling effect which plays a dominant role in the electromagnetic properties of metamaterials [33][34][35][36], notably, in the achievement of negative effective index. Magnetic and electric mode coupling effects in ADMs have been separately studied from each other in the microwave by Zhang et al [34].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in [23][24][25][26], it is shown that by tuning the dimensions of SRR and by implementing a precise fabrication, the magnetic resonance at near infrared and visible frequencies, is achievable. In [27][28][29][30] using effective medium theory, a three-dimensional collection of polaritonic, nonmagnetic spheres have been shown to produce negative permeability at terahertz and infrared frequencies. Furthermore, other structures such as the spherical constellations [31][32][33][34][35], composite medium made of arrays of dielectric spheres [36], a periodic lattice of clusters comprising four silver plasmonic dimers [37] have been used to make metamaterial constituents which provide magnetic polarization in the visible and infrared spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, even though natural optical magnetism vanishes, metamaterials with equivalent magnetic dipolar responses have been widely studied in the past decade. For example, arrays of magnetic meta atoms are employed in engineering bulk effective permeability [2]- [7]. Several studies have been devoted to generating artificial magnetism (i.e., effective relative permeability different from unity) for such structures leading to effective permeability engineering.…”
Section: Introductionmentioning
confidence: 99%